2021
DOI: 10.1111/cdev.13491
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking the Impacts of a Universal Parenting Program on Child Behavior

Abstract: This study examined the theory of change of the ACT Raising Safe Kids parenting program, including whether intervention effects on children's behavior problems were explained by improvements in mothers' reported parenting practices, as well as whether baseline child behavior problems moderated these relations. Adult mothers of 3-to 8-year-old Brazilian children were assigned to the intervention (n = 97) or control (n = 46) groups. Results showed that the intervention improved mothers' perceptions of their pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 32 publications
3
22
0
5
Order By: Relevance
“…The present findings are similar to the findings of a previous study on a face-to-face parenting group program that showed reductions in children's internalizing and externalizing behavior problems mediated by parenting improvements (Altafim et al, 2021). Then, the parenting practice of mothers' emotional and behavioral regulation was the intervention core mechanism that also includes coercive parenting.…”
Section: Discussionsupporting
confidence: 89%
“…The present findings are similar to the findings of a previous study on a face-to-face parenting group program that showed reductions in children's internalizing and externalizing behavior problems mediated by parenting improvements (Altafim et al, 2021). Then, the parenting practice of mothers' emotional and behavioral regulation was the intervention core mechanism that also includes coercive parenting.…”
Section: Discussionsupporting
confidence: 89%
“…It was found that the gender of the children was not a determinant in the child-rearing attitudes of the mothers, and the time spent at home during the quarantine process did not affect the child-rearing attitudes of the mothers in relation to the gender of the children. It was stated in various studies ( Altafim et al, 2021 , Hu and Feng, 2021 ) that the gender of the children was not determinant in the attitudes of mothers towards their children, and mothers displayed similar child-rearing attitudes towards both their sons and their daughters. On the other hand, studies have found that mothers' child-rearing attitudes were more moderate in relation to the gender of their children, while fathers had different child-rearing attitudes, in that they were more authoritarian towards boys ( Ziv & Arbel, 2021 ).…”
Section: Discussionmentioning
confidence: 96%
“…These interventions aim to prevent the problem behaviors of children, increase the parenting satisfaction and ability of parents, and strengthen the bond between children and parents. The vital role of parenting intervention programs in reducing and preventing the problems of children has been confirmed as they help parents reduce the internalization and externalization behaviors of children by improving parental cognition and emotional and behavioral regulation of parenting (Altafim et al, 2021). Among these programs, Triple P has shown its distinguishing advantages because of its evidence-based features and popularity based on public health models (Liu and Guo, 2020).…”
Section: Introductionmentioning
confidence: 99%